Pengaruh Motivasi Kerja, Kepemimpinan dan Budaya Organisasi Terhadap Kepuasan Kerja (Studi Pada Djari-Djari Art of Refelexologi Banjarmasin) - Rudiansyah, Muhammad (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2017)
This study aims to obtain an empirical evidence about the effect of work motivation, leadership and organizational culture on job satisfaction and also to identity which variable has a dominant effect on employee job satisfaction at Djari-djari Art Of Refelexologi Banjarmasin. Population of this study were 36 people who were all employees. This study used a quantitative exploratory descriptive design . Analyzing data used the multiple regression Analysis. In testing hypothesis simultaneonsly, F test was used and T test was used in testing hypothesis patially. The result of this study showed that work motivation, leadership, and organizational culture simultaneonsly have an effect on employee job satisfaction . Whilepartially. Leadership has a dominant effect on employee job satispaction at Djari-djari Art Of Refeloxologi Banjarmasin. Key words : Work Motivation, Leadership, Organizational Culture. Job satisfaction.